Optimised sensor selection for control: A Hardware-in-the-loop realization on FPGA for an EMS system - Michail, Konstantinos; Tzafestas, Spyros G.; Zolotas, Argyrios C.; Deliparaschos, Kyriakos M. (My University, 2013)
This paper presents a Hardware-in-the-loop (HIL) approach on a Field Programmable Gate Array (denoted as FPGA-in-the-loop and abbreviated as FIL) for the optimised sensor selection task of controlling a MAGnetic LEVitation (MAGLEV) system. A recently proposed systematic framework for optimised sensor selection for control and fault tolerance is developed in [1]. The framework was validated using realistic simulations on an electromagnetic suspension system. In this work, the sensor selection framework for control, and practical validation of the controller on FPGA (via HIL concept) applied on an electromagnetic suspension are considered.